Analysis of Shaking Table Tests of Underground Structures considering the Influence of the Structure-Soil Interface - Feng Shuang Guo; Yun Sheng Wang; Chang Bao Wang; LiJuan Wang (Shock and Vibration)
To investigate the seismic performance of underground structures under the action of the structure-soil interface, in this study, experiments were performed using plexiglass structures (two pieces) and a concrete structure (one piece) as the research objects. The surface of one plexiglass structure was prepainted with a layer of cement mortar as the contact surface between the structure and soil, and the other plexiglass structure was not treated and used for comparison. A rigid model box measuring 2.25 m × 2.25 m × 1.5 m was placed on a 3 m × 3 m shaking table, and the box was filled with the configured model soil and the underground structure prepared in advance. Input transverse uniform excitation was imparted to the whole system. A shaking table model test was performed on the underground structures to analyse the acceleration response, stress strain, and earth pressure changes in the underground structure, and the influence of the contact surface on the seismic dynamics of the underground structure was evaluated. The test results showed that under uniform excitation, the dynamic characteristics of the underground structures were greatly affected by the intensity and depth of the seismic waves. (1) When the soil-structure contact was considered, the stress and strain of the structures increased significantly, and the stress-strain value was significantly greater than the stress-strain value of the soil-structure interface in a fully bonded state. (2) There were inconsistencies between the acceleration peak curve of the plexiglass structure considering the contact effect and the acceleration peak curve of the plexiglass structure without considering the contact effect. The difference between the two lies mainly in the corresponding maximum peak acceleration and the Fourier spectrum amplitude. With respect to the value and frequency composition, regardless of whether the input acceleration intensity was 0.2 g or 0.5 g, the peak acceleration of the organic structure was greater when the contact surface effect was considered than without the contact surface effect. Therefore, the structure-soil interface needs to be considered in actual engineering. The presence of the contact surface improves the safety of the structure and is helpful for seismic design. The results of this study provide a basis for further research on the influence of soil-pipe contact on the seismic response of underground structures.